Nanoformulations for dermal delivery of imiquimod: The race of "soft" against "hard" - Petrová, Eliška; Chvíla, Stanislav; Balouch, Martin; Štěpánek, František; Zbytovská, Jarmila (International journal of pharmaceutics, 2023)
Imiquimod (IMQ) is an immunostimulating agent used in the treatment of basal cell carcinoma and actinic keratosis. Due to its low solubility and poor skin bioavailability, the dermal formulation of IMQ remains challenging. In analogy to tyre compounds used in Formula 1 racing, we compare four types of nanosystems belonging to three groups: (i) "hard" nanoparticles in the form of IMQ nanocrystals, (ii) "intermediate" nanoparticles in the form of liposomes and lipid nanocapsules, and (iii) "soft" nanoparticles in the form of a nanoemulsion based on oleic acid. The nanoemulsion and nanocrystals were able to incorporate the highest amount of IMQ (at least 2 wt%) compared to liposomes (0.03 wt%) and lipid nanocapsules (0.08 wt%). Regarding size, liposomes, and lipid nanocapsules were rather small (around 40 nm) whereas nanocrystals and nanoemulsion were larger (around 200 nm). All developed nanoformulations showed high efficiency to deliver IMQ into the skin tissue without undesirable subsequent permeation through the skin to acceptor. Especially, the 2 wt% IMQ nanoemulsion accumulated 129 μg/g IMQ in the skin, compared to 34 μg/g of a 5 wt% commercial cream. The effects of the respective nanoparticulate systems were discussed with respect to their possible diffusion kinetics (Brownian motion vs. settling) in the aqueous phase.
Keywords: Nanocapsules; nanokapsle; Nanocrystals; Skin; imichimod; Nanoemulsion; Lipid nanocapsules; Liposomes; Imiquimod; Oleic acid; Ex vivo permeation study; Lipids; lipidy; kůže; liposomy